Polymorphisms in stromal genes and susceptibility to serous epithelial ovarian cancer: a report from the Ovarian Cancer Association Consortium. - Ernest K Amankwah; Qinggang Wang; Joellen M Schildkraut; Ya-Yu Tsai; Susan J Ramus; Brooke L Fridley; Jonathan Beesley; Sharon E Johnatty; Penelope M Webb; Georgia Chenevix-Trench; Australian Ovarian Cancer Study Group; Laura C Dale; et al. (PLoS ONE)
Alterations in stromal tissue components can inhibit or promote epithelial tumorigenesis. Decorin (DCN) and lumican (LUM) show reduced stromal expression in serous epithelial ovarian cancer (sEOC). We hypothesized that common variants in these genes associate with risk. Associations with sEOC among Caucasians were estimated with odds ratios (OR) among 397 cases and 920 controls in two U.S.-based studies (discovery set), 436 cases and 1,098 controls in Australia (replication set 1) and a consortium of 15 studies comprising 1,668 cases and 4,249 controls (replication set 2). The discovery set and replication set 1 (833 cases and 2,013 controls) showed statistically homogeneous (P(heterogeneity)≥0.48) decreased risks of sEOC at four variants: DCN rs3138165, rs13312816 and rs516115, and LUM rs17018765 (OR = 0.6 to 0.9; P(trend) = 0.001 to 0.03). Results from replication set 2 were statistically homogeneous (P(heterogeneity)≥0.13) and associated with increased risks at DCN rs3138165 and rs13312816, and LUM rs17018765: all ORs = 1.2; P(trend)≤0.02. The ORs at the four variants were statistically heterogeneous across all 18 studies (P(heterogeneity)≤0.03), which precluded combining. In post-hoc analyses, interactions were observed between each variant and recruitment period (P(interaction)≤0.003), age at diagnosis (P(interaction) = 0.04), and year of diagnosis (P(interaction) = 0.05) in the five studies with available information (1,044 cases, 2,469 controls). We conclude that variants in DCN and LUM are not directly associated with sEOC, and that confirmation of possible effect modification of the variants by non-genetic factors is required.